The effect of aerobic exercise on stroke rehabilitation - GEZER, HALİSE HANDE (My University, 2019)
Background and aims To compare the effects of aerobic exercise and conventional exercise that were applied during the rehabilitation process on the aerobic capacity, motor function, activity limitation, quality of life, depression level, and sleep quality in subacute stroke patients. Methods The patients were divided into two groups; aerobic exercise group (n = 22) or conventional exercise group (n = 20). Both groups participated in a conventional stroke rehabilitation program; however, aerobic exercise program was applied only for the patients in group 1. Exercise tolerance test (ETT), respiratory function tests, 6-min walking test (6-MWT), functional independence measure (FIM), Nottingham health profile (NHP), Beck depression scale (BDS), and Pittsburgh sleep quality index (PSQI) were evaluated on admission and discharge. Results The 6-MWT, FIM, some subgroups of NHP, BDS, and PSQI results demonstrated statistical differences in both groups after rehabilitation programs. Significant differences were recorded in terms of changes between admission and discharge values of ETT and BDS in favor of aerobic exercise group. Conclusions Incorporation of aerobic exercises into conventional rehabilitation programs of early stroke patients may provide positive contributions, particularly to mood and aerobic capacity.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; TIP, GENEL & DAHİLİ; Klinik Tıp; Klinik Tıp (MED); MEDICINE, GENERAL & INTERNAL; CLINICAL MEDICINE; Clinical Medicine (MED); Genel Sağlık Meslekleri; Patofizyoloji; Temel Bilgi ve Beceriler; Değerlendirme ve Teşhis; Dahiliye; Aile Sağlığı; Tıp (çeşitli); Genel Tıp; General Health Professions; Pathophysiology; Fundamentals and Skills; Assessment and Diagnosis; Internal Medicine; Family Practice; Medicine (miscellaneous); General Medicine; Aerobic capacity; Exercise; Rehabilitation; Stroke; FUNCTIONAL INDEPENDENCE MEASURE; HEALTH; WALKING; Aerobic capacity; Exercise; Rehabilitation; Stroke